Research on seismic behavior of special-shaped CFST column to H-section steel beam joint. Issue 13 (October 2021) - Cheng, Yu; Yang, Yuanlong; Li, Binyang; Liu, Jiepeng
To investigate the seismic behavior of joint between special-shaped concrete-filled steel tubular (CFST) column and H-section steel beam, a pseudo-static test was carried out on five specimens with scale ratio of 1:2. The investigated factors include stiffening types of steel tube (multi-cell and tensile bar) and connection types (exterior diaphragm and vertical rib). The failure modes, hysteresis curves, skeleton curves, stress distribution, and joint shear deformation of specimens were analyzed to investigate the seismic behaviors of joints. The test results showed the connections of exterior diaphragm and vertical rib have good seismic behavior and can be identified as rigid joint in the frames with bracing system according to Eurocode 3. The joint of special-shaped column with tensile bars have better seismic performance by using through vertical rib connection. Furthermore, a finite element model was established and a parametric analysis with the finite element model was conducted to investigate the influences of following parameters on the joint stiffness: width-to-thickness ratio of column steel tube, beam-to-column linear stiffness ratio, vertical rib dimensions, and axial load ratio of column. Lastly, preliminary design suggestions were proposed.